Early intervention in psychiatric disorders across cultures - Chen, Eric Yu-hai; Ventriglio, Antonio; Bhugra, Dinesh (Oxford cultural psychiatry series., 2019)
Evidence indicates a correlation between early intervention and improved response in psychiatric disorders. Yet the majority of evidence is from high-income countries, and there is a lack of evidence and resources on the impact of early intervention across cultures and in low- and middle-income countries. Early Intervention in Psychiatric Disorders across Cultures aims to bridge this gap by focusing on the evidence and methods of intervention in less affluent countries. It covers mood disorders, personality disorders, addictions, and other psychiatric conditions, whilst most research has focused on psychoses and bipolar disorder. Over 17 chapters, this resource guides the reader through an array of approaches to early intervention, from brain imaging and available care pathways, to cultural and societal factors. Part of the Oxford Cultural Psychiatry series, this resource offers readers a picture of the current health care pathways available as well as social, cultural, and ethical considerations to apply in practice--from publisher's website.